Anti-ion oxygen hydrotalcite coating and preparation method and application thereof
By forming a hydrotalcite coating with a highly consistent nanosheet stacking arrangement structure on the surface of the spacecraft, the problem of the existing anti-atomic oxygen coating being easy to peel and crack is solved, and excellent anti-atomic oxygen performance and high flexibility are achieved Coating meets the design requirements of long life and high reliability of spacecraft.
Patent Information
- Application Number
- CN202210207848.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-03
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-03-03
AI Technical Summary
The existing anti-atomic oxygen coatings are prone to peeling and cracking in low-Earth orbit environments, making it difficult to meet the design requirements of long-life and high reliability of spacecraft.
The hydrotalcite coating with a highly consistent nanosheet stack arrangement structure is adopted, and the porous coating formed by cross-linking the hydrotalcite nanosheets with a silane coupling agent enhances the mechanical strength and flexibility of the coating and prevents peeling and cracking.
The coating with excellent anti-atomic oxygen performance, high flexibility and strong binding force is achieved, which significantly improves the service life and reliability of the spacecraft in low-Earth orbit environments.
Smart Images

Figure CN116731541B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an anti-atomic oxygen hydrotalcite coating and a preparation method and application thereof, and specifically to an anti-atomic oxygen hydrotalcite coating with a fish scale-like, non-dense structure and a preparation method thereof, which is mainly used in low-orbit spacecraft affected by atomic oxygen corrosion and belongs to the technical field of aerospace material application. Background Art
[0002] Polymer materials have the advantages of good flexibility, light weight, low cost, and easy processing. They are important components of various fields such as household appliances, electronic information, automobile industry, aerospace, etc. As an important material closely related to the national economy, high-tech technology and modern life, they have played a huge role in various fields. For example, polyimide (PI) has outstanding comprehensive properties. Its high and low temperature stability, high strength, good flexibility, light weight, radiation resistance, and low outgassing rate make it an irreplaceable polymer material in the aerospace field and widely used in thermal control, power supply and structural systems. However, in the space environment of low Earth orbit (LEO), there is a large amount of atomic oxygen (AO) with strong oxidizing properties. Atomic oxygen can easily cause serious corrosion to polymers, affect the normal operation of spacecraft and reduce its service life, and is therefore considered to be the most serious factor threatening low-orbit spacecraft. Therefore, with the rapid development of space stations, Fengyun satellites, ultra-low-orbit and earth-to-earth round-trip spacecraft, there are more and more low-orbit long-life spacecraft, and the protection technology against the threat of atomic oxygen corrosion is also receiving more and more attention.
[0003] When atomic oxygen collides with a high-speed spacecraft in orbit, the bombardment energy of atomic oxygen can reach 4 to 5 eV. When atomic oxygen with high energy and strong oxidizing properties acts on the surface of polymer materials, it is easy to corrode, resulting in mass loss and performance degradation. Atomic oxygen protection technology mainly improves the polymer's resistance to atomic oxygen corrosion by directly introducing or indirectly generating atomic oxygen inert substances. Atomic oxygen inert substances do not react with atomic oxygen, and at the same time isolate atomic oxygen to prevent it from invading the matrix, thereby improving the matrix's resistance to atomic oxygen corrosion.
[0004] At present, atomic oxygen protection technology can be roughly divided into two categories: polymer matrix modification and surface protection. The matrix modification method, such as the patent "A method for preparing an antiproton oxygen polyimide hybrid film containing a POSS structure" (CN102731809A), discloses an antiproton oxygen polyimide material containing a cage-type silsesquioxane group. Such matrix modification methods generally require changing the precursor components of polyimide, grafting and blocking modified groups on its main chain or side chain, but this will affect the mechanical properties of the polymer base film, making it difficult to form a dense protective layer, and the protective performance is poor. And the organic precursors used in such methods are generally expensive and not suitable for widespread application. Unlike matrix modification, surface protection can provide protection for the matrix without affecting the original performance of the matrix, so it has been widely studied and applied. Inorganic protective coatings have atomic oxygen inertness and are easy to achieve stable and excellent antiproton oxygen performance. However, the flexibility of inorganic coatings is generally poor, and they are easily peeled off and cracked by stress, thereby limiting their application. Therefore, given the excellent performance of inorganic coatings in preventing atomic oxygen corrosion, if the easy peeling and cracking problem of inorganic coatings can be solved, it is expected to meet the long life and high reliability design requirements of atomic oxygen-resistant coatings on spacecraft. Therefore, the invention of an inorganic atomic oxygen-resistant coating that prevents peeling and cracking is of great significance and practical need. Summary of the invention
[0005] The technical problem to be solved by the present invention is to provide an anti-proto-oxygen hydrotalcite coating and its preparation method and application, based on the characteristics of highly active AO tending to adsorb and bond, which is different from the traditional atomic oxygen protective layer pursuing a dense idea, and through the rarely reported idea of regulating the micro-nano structure to solve the problem of easy detachment and cracking of inorganic coatings. The coating has a highly oriented nanosheet stacked arrangement structure, has excellent anti-proto-oxygen performance, and has the characteristics of good flexibility, strong bonding with the substrate, and easy operation.
[0006] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0007] The anti-proton oxygen hydrotalcite coating comprises: a porous coating formed on the surface of a polymer matrix by cross-linking at least one of hydrotalcite nanosheets or hydrotalcite-like nanosheets and a silane coupling agent; preferably, the silane coupling agent can react and bond with the polymer matrix or the hydrotalcite coating, for example, the polymer matrix is a polymer matrix containing hydroxyl groups and carboxyl groups or a polymer matrix that can be modified to generate hydroxyl groups and carboxyl groups, and the silane coupling agent is an aminohydrocarbon silane having an amino group.
[0008] In the present invention, the hydroxyl groups on the surface of the hydrotalcite nanosheets or hydrotalcite-like nanosheets and the hydroxyl groups generated by the hydrolysis of the aminohydrocarbon silane coupling agent are dehydrated to form bonds, thereby improving the mechanical strength of the hydrotalcite nanosheets or hydrotalcite-like nanosheet coating. At the same time, the hydroxyl groups, carboxyl groups on the surface of the selected polymer matrix and the terminal amino groups of the silane coupling agent are dehydrated and bonded to improve the bonding strength between the hydrotalcite nanosheets or hydrotalcite-like nanosheet coating and the polymer matrix. Most importantly, the highly oriented stacked structure formed by cross-linking at least one of the hydrotalcite nanosheets or hydrotalcite-like nanosheets and the silane coupling agent greatly prolongs the erosion path of atomic oxygen and increases the obstacles on the erosion path, making the coating extremely excellent in anti-proton oxygen erosion performance and extremely low in mass loss; at the same time, the structure has certain gaps, which can allow appropriate staggered sliding motion between the nanosheets to absorb and release stress, so the coating flexibility is significantly improved and has excellent anti-stripping and cracking performance.
[0009] Preferably, the chemical composition of the hydrotalcite nanosheets or hydrotalcite-like nanosheets is [M 2+ 1-x M 3+ x (OH)2] x+ A n- x / n mH2O, where M 2+ is a divalent metal cation, preferably selected from Mg 2+ 、Ni 2+ 、Co 2+ 、Zn 2+ , Cu 2+ At least one of 3+ is a trivalent metal cation, preferably selected from Al 3+ Cr 3+ , Fe 3+ Sc 3+ At least one of n- is an anion, preferably selected from CO3 2- 、NO3 - , Cl - OH - 、SO4 2- PO4 3- 、C6H4(COO)2 2- At least one of the following; x is in the range of 0.1 to 0.5, preferably 0.2 to 0.33; more preferably, the divalent metal cation is Mg 2+ , the trivalent metal cation is Al 3+ , most preferably Mg 2+ :Al 3+ =2:1.
[0010] Preferably, the sheet of the hydrotalcite nanosheet or hydrotalcite-like nanosheet is nearly regular hexagonal or circular; the diameter of the circumscribed circle of the circular or nearly hexagonal shape is between 100 and 500 nm, and the ratio of diameter to thickness is 15-40.
[0011] Preferably, the antigenic oxygen-resistant hydrotalcite coating further comprises a silane coupling agent modified layer distributed between the polymer matrix and the porous coating; the thickness of the silane coupling agent modified layer is 20 nm to 1000 nm.
[0012] Preferably, the silane coupling agent is selected from at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-aminoethyl-3-aminopropyltriethoxysilane, and 3-aminopropylmethyldiethoxysilane, preferably aminoalkylsilane 3-aminopropyltriethoxysilane.
[0013] Preferably, the ratio of at least one of the hydrotalcite nanosheets or hydrotalcite-like nanosheets to the silane coupling agent in the porous coating is (5-40) mg: (5-30) μL. That is, the ratio of at least one of the hydrotalcite nanosheets or hydrotalcite-like nanosheets to the silane coupling agent is 1 mg: 6 μL to 8 mg: 1 μL.
[0014] Preferably, the polymer matrix that can be modified to generate hydroxyl groups and carboxyl groups is a polymer containing an imide ring and / or an ester group;
[0015] The polymer matrix containing hydroxyl and carboxyl groups is prepared by treating a polymer containing imide rings or / and ester groups with alkali / acid in two steps; more preferably, the polymer containing imide rings or / and ester groups is polyimide, polyester, or polyethylene terephthalate.
[0016] Preferably, the alkali / acid two-step treatment includes: first reacting and modifying the polymer matrix in an alkali solution for 0.5 to 3 hours at room temperature, and then reacting and modifying it in an acetic acid solution for 0.5 to 3 hours; preferably, the alkali solution is a sodium hydroxide solution with a concentration of 0.5 to 2 mol / L, and the acid solution is an acetic acid solution with a concentration of 0.5 to 2 mol / L.
[0017] In another aspect, the present invention provides a method for preparing an anti-oxygen hydrotalcite coating, comprising:
[0018] A silane coupling agent is added to an aqueous dispersion containing at least one of hydrotalcite nanosheets or hydrotalcite-like nanosheets and mixed, and then coated on the surface of a polymer matrix containing hydroxyl groups and carboxyl groups or a polymer matrix that can be modified to generate hydroxyl groups and carboxyl groups. After spin coating and drying, the coating is heat treated at 80 to 250° C. for 3 to 12 hours to obtain an anti-protonypic hydrotalcite coating.
[0019] Preferably, the concentration of the aqueous dispersion containing at least one of hydrotalcite nanosheets or hydrotalcite-like nanosheets is 5-40 mg / mL, preferably 18 mg / mL; the mixing method is stirring, and the stirring speed is 200-400 rpm.
[0020] Preferably, the coating is performed at least once; the coating includes spin coating, drip coating, spray coating, scraping coating or static pulling; preferably, the spin coating speed is 600-1400 rpm, and the spin coating time is 6-18 seconds each time; the drying is performed at least once, the temperature is 60-120°C, and the drying time is 10-30 seconds each time.
[0021] On the other hand, the present invention also provides an application of the above-mentioned antiproto-oxygen hydrotalcite coating in the field of space environment. Different from the conventional dense antiproto-oxygen coating, the coating involved in the present invention is composed of protective units of inorganic magnesium-aluminum hydrotalcite nanosheets and amino-hydrocarbon silane coupling agents, and has a non-dense micro-nano structure formed by a stacked arrangement of nanosheets with highly consistent orientation, which can prevent cracking due to internal stress; at the same time, the cross-linking agent amino-hydrocarbon silane coupling agent can enhance the interface adhesion between the coating and the substrate to prevent the occurrence of peeling. The main body of the coating is an inorganic magnesium-aluminum hydrotalcite nanosheet layer, with low raw material price, simple process, easy operation, and excellent antiproto-oxygen / anti-stripping and cracking performance, and can be widely used in the aerospace field.
[0022] Beneficial effects:
[0023] (1) The fish-scale-like, non-densely structured anti-oxygen hydrotalcite coating provided by the present invention has excellent anti-oxygen performance because its main body is an oriented densely packed inorganic hydrotalcite nanosheet material;
[0024] (2) Unlike existing dense inorganic coatings that are prone to peeling and cracking, this coating material has a highly oriented nanosheet stacking structure, and the sheets can be properly staggered and slipped, so its flexibility is significantly improved, which can prevent cracking during hot and cold cycles and bending. The coating and the polyimide matrix are bonded through a modified layer, with high bonding strength and excellent anti-peeling performance;
[0025] (3) The raw materials of the coating are cheap, the process is simple and the operation is convenient. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is an electron microscope photograph of the surface of the antigenic magnesium-aluminum hydrotalcite coating with a fish-scale-like non-dense structure in Example 1. It can be seen from the figure that the coating is stacked with highly oriented nanosheets and has a fish-scale-like structure;
[0027] Figure 2This is an EDS image of the surface of the antigenic oxygen magnesium aluminum hydrotalcite coating with a fish scale-like non-dense structure in Example 1. It can be seen from the image that the coating contains elements such as magnesium, aluminum, and silicon, wherein magnesium, aluminum, and silicon account for 14.87, 7.48, and 2.72 at% respectively;
[0028] Figure 3 This is a light microscope picture of the fish-scale-like non-dense structure of the antigenic oxygen magnesium aluminum hydrotalcite coating after the bending test in Example 1. After repeated bending 180° on a cylinder with a diameter of 2 mm for 500 times, the coating did not peel off or crack, and had excellent flexibility and bonding strength with the substrate;
[0029] Figure 4 This is a light microscope picture of the fish-scale-like non-dense structured antigenic magnesium-aluminum hydrotalcite coating after the hot and cold cycle test in Example 1. After 100 cycles in a hot and cold environment of ±100°C, the coating did not peel off or crack, and had excellent resistance to thermal stress.
[0030] Figure 5 This is a light microscope picture of the fish-scale-like non-dense structure of the antigenic oxygen magnesium aluminum hydrotalcite coating after the cross-hatch method was used to test the adhesion of the coating. The cut part of the coating is completely smooth without any grid stratification, and its adhesion is the highest level 0, and the bonding strength between the coating and the substrate is high;
[0031] Figure 6 This is a light microscope picture of the fish-scale-like non-dense structure of the antigenic oxygen magnesium aluminum hydrotalcite coating without amino hydrocarbon silane coupling agent in Example 5 after the adhesion test by the cross-hatch method. There is a small part of the coating peeling off at the intersection of the cut, and the adhesion is level 1;
[0032] Figure 7 This is a light microscope comparison of the fish-scale-like non-dense structure of the antigenic oxygen magnesium aluminum hydrotalcite coating before and after the ground atomic oxygen simulation test in Example 1. After the erosion of atomic oxygen, the surface morphology of the coating has no obvious damage, no peeling and cracking occurs, and the stability is relatively strong;
[0033] Figure 8 The schematic diagram of the structure of an antigenic oxygen hydrotalcite coating with a fish scale-like non-dense structure disclosed in the present invention. DETAILED DESCRIPTION
[0034] The present invention is further described below by the following embodiments. It should be understood that the following embodiments are only used to illustrate the present invention, but not to limit the present invention.
[0035] In the present disclosure, the antigenic oxygen hydrotalcite coating comprises: a porous coating composed of a laminated structure formed by hydrotalcite nanosheets or hydrotalcite-like nanosheets with a certain sheet size and a small amount of silane coupling agent. The surface morphology of the antigenic oxygen hydrotalcite coating is a fish-scale-like sheet structure, and a non-dense structure with certain pores. Moreover, the antigenic oxygen hydrotalcite coating is attached to the surface of a polymer matrix containing hydroxyl or carboxyl groups on the surface. At this time, the coating and the matrix are mainly bonded by the amino group of the silane coupling agent and the hydroxyl and carboxyl groups originally or modified from the matrix, thereby enhancing the interfacial bonding force. Different from the conventional dense antigenic oxygen coating, the coating involved in the present invention is composed of protective unit hydrotalcite or hydrotalcite-like nanosheets and amino hydrocarbon silane coupling agents, and has a non-dense micro-nano structure formed by a laminated arrangement with highly consistent nanosheet orientation, which can prevent cracking due to internal stress; at the same time, the cross-linking agent amino hydrocarbon silane coupling agent can enhance the interfacial adhesion between the coating and the matrix, and prevent the occurrence of peeling. The main body of the coating is inorganic hydrotalcite or hydrotalcite-like nanosheets. The raw materials are cheap, the process is simple, the operation is convenient, and it has excellent anti-oxidation / anti-flaking and cracking properties, and can be widely used in the aerospace field.
[0036] In an optional embodiment, the chemical composition of the hydrotalcite nanosheets or hydrotalcite-like nanosheets of a certain size can be expressed as [M 2+ 1-x M 3+ x (OH)2] x+ A n- x / n ·mH2O. 2+ For divalent metal cations, such as Mg 2+ 、Ni 2+ 、Co 2 + 、Zn 2+ , Cu 2+ etc.; M 3+ For trivalent metal cations, such as Al 3+ Cr 3+ , Fe 3+ Sc 3+ etc. n- Anions, such as CO3 2- 、NO3 - , Cl - OH - 、SO4 2- PO4 3- 、C6H4(COO)2 2- Inorganic and organic ions and complex ions; x ranges from 0.1 to 0.5, preferably from 0.2 to 0.33. The preferred composition is a hydrotalcite-like nanosheet with a magnesium-aluminum ratio of 2:1, wherein the divalent metal cation, trivalent metal cation, and anion are Mg2+ 、Al 3+ , Cl - , and Mg 2+ :Al 3+ =2:1.
[0037] In an optional embodiment, the hydrotalcite or hydrotalcite-like nanosheets of a certain size can be prepared in large quantities by a two-step co-precipitation and hydrothermal method, and the sheet layers are nearly regular hexagons or circles, the circle diameter or the hexagonal circumscribed circle diameter is in the range of 100nm to 500nm, and the diameter to thickness ratio is 15 to 40.
[0038] In an optional embodiment, the polymer matrix containing hydroxyl and carboxyl groups can be polyimide, polyester, polyethylene terephthalate, or other polymers containing imide rings and ester groups that can generate carboxyl groups on the surface after two-step alkali and acid treatment.
[0039] In an alternative embodiment, the thickness of the hydrotalcite coating layer may be 200 nm to 10 μm.
[0040] The following is an exemplary description of the fish-scale-like, non-dense structure of the anti-oxygen hydrotalcite coating of the present invention.
[0041] Alkali / acid modification of polymer matrix. Place polyimide, polyester, polyethylene terephthalate and other matrices in 0.5-2 mol / L (e.g. 1 mol / L) sodium hydroxide solution and 0.5-2 mol / L (e.g. 1 mol / L) acetic acid solution for reaction modification for 0.5-3 hours (e.g. 1 h) to obtain an alkali / acid modified polymer matrix. When changing the solution and after the modification is completed, use deionized water and anhydrous ethanol to repeatedly wash to remove the residual modified solution. After drying at room temperature, carry out subsequent coating.
[0042] Preparation of an aqueous dispersion containing hydrotalcite nanosheets or / and hydrotalcite-like nanosheets. Preferably, the dispersion is prepared by a two-step method of coprecipitation and hydrothermal method. Taking the preferred magnesium-aluminum hydrotalcite-like nanosheets as an example, the steps of preparing the hydrotalcite-like nanosheets by the two-step method of coprecipitation and hydrothermal method include: preparing a solution of magnesium chloride hexahydrate, aluminum chloride hexahydrate, and water in a molar ratio of (3-x): 3x: 350 (where x ranges from 0.1 to 0.5, preferably 0.2 to 0.33), adding ammonia water and stirring to adjust the pH to 9 to 10, and standing after stirring. The resulting suspension is centrifuged and washed with deionized water to a pH of 8 to 9. It is then placed in an oven at 80 to 200°C for hydrothermal treatment for 24 hours.
[0043] A certain amount of aminosilane as a crosslinking agent is added to the aqueous dispersion containing hydrotalcite nanosheets or / and hydrotalcite-like nanosheets, and then after stirring for a certain period of time, it is coated on the polymer substrate modified by alkali / acid two steps to form a wet film. The stirring speed is 200-400 rpm and the time is 30-90 minutes (for example, 60 minutes).
[0044] After each layer of wet film is initially dried, it is coated again, and after multiple coatings, it is heat treated in air atmosphere. Finally, a fish-scale-like, non-dense structure of anti-oxygen hydrotalcite coating is obtained. The initial drying process of the wet film is processed in an oven.
[0045] In an optional embodiment, the coating method is any one of spin coating, drop coating, spray coating, blade coating or hysteresis pull-up. The coating process is repeated 3 to 9 times, preferably 6 times.
[0046] In an optional embodiment, the heat treatment temperature may be a temperature value within 80 to 250° C. or a gradient change formed by several temperature values. The total time of the heat treatment may be 3 to 12 hours. Preferably, the heat treatment process is 80° C., 110° C., 150° C. for 1 hour, 1 hour, and 3 hours, respectively.
[0047] Specifically, magnesium chloride hexahydrate, aluminum chloride hexahydrate, 3-aminopropyltriethoxysilane, alkali / acid modified polyimide film, spin coating method are used as magnesium source and aluminum source, cross-linking agent, polymer matrix, and coating method for preparing magnesium-aluminum hydrotalcite nanosheets, respectively, to exemplify a method for preparing a fish-scale-like, non-dense structured antigenic oxygen hydrotalcite coating.
[0048] Preparation of magnesium aluminum hydrotalcite nanosheet dispersion. 0.6449g magnesium chloride hexahydrate and 1.9314g aluminum chloride hexahydrate were dissolved in 50mL deionized water to prepare a precursor solution. Ammonia water was quickly added within 5s and the pH was adjusted to 9-10 by stirring. After stirring for 15min, the solution was allowed to stand for aging for 1h. The obtained white suspension was centrifuged and washed with deionized water several times to a pH of 8-9. After washing, a certain amount of deionized water was added to the precipitate and stirred evenly to obtain a dispersion with a mass concentration of 5-40mg / mL (such as 18mg / mL). The dispersion was then placed in an oven at a temperature of 80-150℃ (such as 80℃) for hydrothermal heating for 24h. Finally, a magnesium aluminum hydrotalcite nanosheet dispersion with a nearly regular hexagonal shape and a circumscribed circle diameter in the range of 100-500nm (such as 120nm) and a diameter-to-thickness ratio of 15-40 (such as 18) was obtained.
[0049] Preparation of fish-scale-like, non-densely structured anti-ionic oxygen hydrotalcite coating. Add 3-aminopropyltriethoxysilane to the above-mentioned magnesium-aluminum hydrotalcite nanosheet dispersion to a concentration of 5 to 30 μL / mL (such as 10 μL / mL). After stirring for 60 minutes, 6 drops of solution are added each time and spin-coated on a 20×20mm alkali / acid-modified polyimide film substrate at a speed of 1000 rpm for 12 seconds. The formed wet film is treated in an 80°C drying oven for 20 seconds for preliminary drying, and then spin-coated and dried again, for a total of 6 times. It is then placed in an air atmosphere at 80, 110, and 150°C for heat treatment for 1h, 1h, and 3h, respectively. Finally, the above-mentioned fish-scale-like, non-densely structured anti-ionic oxygen hydrotalcite coating can be obtained.
[0050] The advantages of the method of the present invention are: commercially available metal chloride salts are used as raw materials, and the raw materials are inexpensive; the precursor is prepared and the coating is formed by a wet chemical method, which has low equipment requirements, simple process and convenient operation; the prepared magnesium-aluminum hydrotalcite nanosheet coating has uniform film formation, no agglomeration, and exhibits excellent anti-proton oxygen performance; the use of an amino-hydrocarbon silane coupling agent not only strengthens the cross-linking degree between magnesium-aluminum hydrotalcite sheets, significantly improves the flexibility of the coating, but also enables the coating to be firmly bonded to the surface of the surface-modified polyimide, significantly improving the adhesion of the coating.
[0051] Test: A ground-based atomic oxygen simulation test equipment was used to characterize the sample's resistance to atomic oxygen corrosion, and a precision balance was used to measure the mass loss. Space hot and cold cycle simulation test equipment was used to characterize the sample's resistance to thermal stress cracking. The QTY-10A bending tester was used to test the sample's resistance to bending stress cracking. The hundred-grid knife scratch method was used to characterize the bonding strength between the coating and the substrate, specifically, the scratches were followed by sticking with 3M610 tape for observation. A scanning electron microscope was used to observe the surface morphology of the sample.
[0052] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above content of the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific values exemplified below.
[0053] Example 1
[0054] (1) Preparation of an aqueous dispersion (concentration of 18 mg / mL) of magnesium-aluminum hydrotalcite nanosheets (circumscribed circle diameter 140 nm). 0.6449 g of magnesium chloride hexahydrate and 1.9314 g of aluminum chloride hexahydrate were dissolved in 50 mL of deionized water to prepare a precursor solution. Ammonia water was quickly added within 5 seconds and the pH was adjusted to 9-10 by stirring. After stirring for 15 minutes, the solution was allowed to stand for aging for 1 hour. The resulting white suspension was centrifuged and washed with deionized water several times until the precipitate had a pH of 8-9. After washing, a certain amount of deionized water was added to the precipitate and stirred evenly to obtain a dispersion with a mass concentration of 18 mg / mL. The dispersion was then hydrothermaled in an oven at 80°C for 24 hours. Finally, a magnesium-aluminum hydrotalcite nanosheet dispersion with a nearly regular hexagonal shape and a circumscribed circle diameter of approximately 120 nm and a diameter-to-thickness ratio of approximately 18 was obtained.
[0055] (2) Add 3-aminopropyltriethoxysilane (50 μL) to the above-mentioned magnesium aluminum hydrotalcite nanosheet dispersion (5 mL) (wherein the ratio of at least one of the talc nanosheets or hydrotalcite nanosheets to the silane coupling agent is 9 mg:5 μL). After stirring for 60 minutes, 6 drops of the solution are added each time and spin-coated on a 20×20 mm alkali / acid modified polyimide film substrate at a speed of 1000 rpm for 12 seconds. The formed wet film is treated in an oven at 80°C for 20 seconds for preliminary drying, and then spin-coated and dried again, for a total of 6 times. It is then placed in an air atmosphere at 80, 110, and 150°C for heat treatment for 1 hour, 1 hour, and 3 hours, respectively. Finally, the above-mentioned fish-scale-like, non-dense structured anti-proton oxygen hydrotalcite coating can be obtained. Among them, the thickness of the aminohydrocarbon silane modified layer is about 1000 nm.
[0056] Example 2
[0057] The preparation process of the fish-scale-like, non-dense structured anti-oxygen hydrotalcite coating in Example 2 is similar to that in Example 1, except that the hydrothermal temperature in step (1) is 110°C.
[0058] Example 3
[0059] The preparation process of the fish-scale-like, non-dense structured anti-oxygen hydrotalcite coating in Example 3 is similar to that in Example 1, except that the hydrothermal temperature in step (1) is 130°C.
[0060] Example 4
[0061] The preparation process of the fish-scale-like, non-dense structured anti-oxygen hydrotalcite coating in Example 4 is similar to that in Example 1, except that the hydrothermal temperature in step (1) is 150° C. In this example, the diameter of the hydrotalcite nanosheets is too large, so that the bending strength of the bonding layer at the interface between the coating and the substrate is significantly reduced, and the crack size is significantly larger than that of other examples with lower hydrothermal temperatures.
[0062] Example 5
[0063] The preparation process of the fish-scale-like, non-dense structured anti-oxygen hydrotalcite coating in Example 5 is similar to that in Example 1, except that 3-aminopropyltriethoxysilane is not added in step (2). In this example, the bonding strength between the coating and the substrate is reduced without the addition of a cross-linking agent, and the cross-hatch test rating is reduced to level 1.
[0064] Example 6
[0065] The preparation process of the fish-scale-like, non-densely structured antigenic oxygen hydrotalcite coating in Example 6 refers to Example 1, with the only difference being that the content of 3-aminopropyltriethoxysilane added in step (2) is 150 μL (wherein the ratio of at least one of talc nanosheets or hydrotalcite-like nanosheets to the silane coupling agent is 3 mg:5 μL).
[0066] Example 7
[0067] The preparation process of the fish-scale-like, non-dense structured anti-proton oxygen hydrotalcite coating in Example 7 is similar to that in Example 1, the only difference is that the content of 3-aminopropyltriethoxysilane added in step (2) is 300 μL (wherein the ratio of at least one of talc nanosheets or hydrotalcite-like nanosheets to the silane coupling agent is 3 mg: 10 μL). In this example, the excessive amount of cross-linking agent significantly increases the mass loss of the coating, and the anti-proton oxygen performance is significantly reduced.
[0068] The raw materials listed in the present invention, as well as the upper and lower limits and interval values of the raw materials of the present invention, and the upper and lower limits and interval values of the process parameters can realize the present invention, and the embodiments are not listed one by one here. The data of the listed embodiments are shown in Table 1:
[0069]
[0070] Finally, it is necessary to explain here that the above embodiments are only used to further illustrate the technical solution of the present invention in detail and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by technicians in this field based on the above content of the present invention all fall within the scope of protection of the present invention.
Claims
1. An anti-oxygen hydrotalcite coating, characterized in that: include: A porous coating formed on the surface of a polymer matrix and composed of a laminated structure formed by cross-linking at least one of hydrotalcite nanosheets or hydrotalcite-like nanosheets and a silane coupling agent; The polymer matrix is a polymer matrix containing hydroxyl groups and carboxyl groups, and the silane coupling agent is aminohydrocarbon silane having amino groups; The anti-oxygen hydrotalcite coating further comprises a silane coupling agent modified layer distributed between the polymer matrix and the porous coating.
2. The anti-oxygen hydrotalcite coating according to claim 1, characterized in that: The chemical composition of the hydrotalcite nanosheet or hydrotalcite-like nanosheet is [M 2+ 1-x M 3+ x (OH)2] x+ A n- x / n mH2O, where M 2+ is a divalent metal cation selected from Mg 2+ 、Ni 2+ 、Co 2+ 、Zn 2+ , Cu 2+ At least one of 3+ is a trivalent metal cation selected from Al 3+ Cr 3+ , Fe 3+ Sc 3+ At least one of n- is an anion selected from CO3 2- 、NO3 - , Cl - OH - 、SO4 2- PO4 3- 、C6H4(COO)2 2- At least one of the following; the range of x is between 0.1 and 0.
5.
3. The anti-oxygen hydrotalcite coating according to claim 1, characterized in that: The sheet layer of the hydrotalcite nanosheet or hydrotalcite-like nanosheet is nearly regular hexagonal or circular; the diameter of the circumscribed circle of the circular or nearly hexagonal shape is between 100 and 500 nm, and the ratio of the diameter to the thickness is 15-40.
4. The anti-oxygen hydrotalcite coating according to claim 1, characterized in that: The thickness of the silane coupling agent modified layer is 20 nm to 1000 nm.
5. The anti-oxygen hydrotalcite coating according to claim 1, characterized in that: The silane coupling agent is selected from at least one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, N-aminoethyl-3-aminopropyltriethoxysilane and 3-aminopropylmethyldiethoxysilane.
6. The anti-oxygen hydrotalcite coating according to claim 1, characterized in that: The ratio of at least one of the hydrotalcite nanosheets or the hydrotalcite-like nanosheets to the silane coupling agent in the porous coating is (5-40) mg: (5-30) μL.
7. The anti-oxygen hydrotalcite coating according to claim 1, characterized in that: The polymer matrix containing hydroxyl and carboxyl groups is prepared by treating an imide ring or / and ester group-containing polymer through two steps of alkali / acid; the imide ring or / and ester group-containing polymer is polyimide, polyester or polyethylene terephthalate; the two-step alkali / acid treatment comprises: firstly reacting and modifying the imide ring or / and ester group-containing polymer in an alkali solution for 0.5 to 3 hours at room temperature, and then reacting and modifying it in an acid solution for 0.5 to 3 hours; the alkali solution is a sodium hydroxide solution with a concentration of 0.5 to 2 mol / L, and the acid solution is an acetic acid solution with a concentration of 0.5 to 2 mol / L.
8. A method for preparing the anti-oxygen hydrotalcite coating according to claim 1, characterized in that: include: A silane coupling agent is added to a water dispersion containing at least one of hydrotalcite nanosheets or hydrotalcite-like nanosheets and mixed, and then coated on the surface of a polymer matrix containing hydroxyl and carboxyl groups. After drying, the coating is heat-treated at 80 to 250° C. for 3 to 12 hours to obtain an anti-proton hydrotalcite coating.
9. The preparation method according to claim 8, characterized in that The concentration of the aqueous dispersion containing at least one of hydrotalcite nanosheets or hydrotalcite-like nanosheets is 5-40 mg / mL; the mixing method is stirring, and the stirring speed is 200-400 rpm.
10. The preparation method according to claim 8, characterized in that: The coating is performed at least once; the coating includes spin coating, drip coating, spray coating, scraping coating or static pulling; the spin coating speed is 600 to 1400 rpm, and each spin coating time is 6 to 18 seconds; the drying is performed at least once, the temperature is 60 to 120° C., and the drying time is 10 to 30 seconds each time.
11. Use of the anti-oxygen hydrotalcite coating as claimed in claim 1 in the field of space environment.
Citation Information
Patent Citations
Preparation method of atomic oxygen-resistant polyimide hybrid films containing POSS (polyhedral oligomeric silsesquioxanes) structures
CN102731809A
Method for preparing ZnAl-LDHs film layer on surface of titanium alloy
CN113684476A
Coated metal plate and construction panel
JP2011224548A